Enterprise Data Centralization in Mortgage Operations: A Case Study of Real-Time Integration Using Salesforce at Temple View Capital - Ravi Chandra Chinta (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive case study examining the implementation of a centralized data architecture within a mortgage lending institution, focusing on the transformation from fragmented, batch-processed data integration to a real-time, unified system. The article analyzes the strategic deployment of Salesforce as a central platform, incorporating point-to-point integrations with multiple external systems including loan origination and servicing platforms. By implementing unique identifiers based on SSN and EIN, replacing the previous email-based identification system, the organization achieved significant improvements in data accuracy and accessibility. The article explores the technical architecture, implementation methodology, and organizational impact of this transformation. article demonstrate enhanced operational efficiency across multiple departments, including sales, draw&rehab, underwriting, valuations, and servicing teams, through improved data accessibility and reduced latency. The article contributes to the body of knowledge in enterprise data integration within financial services, offering insights into successful implementation strategies and addressing common challenges in modern mortgage operations. This article provides valuable insights for financial institutions seeking to optimize their data architecture while maintaining regulatory compliance and operational efficiency.